Parental Influence on Adolescents’ Career Choices - Bhagawati, Shubhangi; Puranik, Deepti (JOURNAL OF INDIAN EDUCATION, 2022)
This paper explores parental influence on adolescents’ career choices. Choosing a career is considered to be one of the crucial phases in a person’s life and hence it is an important decision. The adolescent period is considered, since it has been explored, as a critical period, filled with a lot of developments and transitions that occur in one’s life. Parents play a dynamic role in forming of an adolescent’s career, and they are the ones with whom we have day-today correspondence since childhood and are involved in some or the other decisions in our life, it is crucial to look into the parent-child relationship. This paper tries to explore three main relationships: first is the relationship between perceived parental influence on adolescents’ career choices and emotional independence from parents. Second it tries to explore the relationship between perceived parental influence and vocational commitment of adolescents. Thirdly, it explores the relationship between vocational commitment and emotional independence from parents.